‘Race’ and the Politics of Land Loss: Colonising Discourses for Patuheuheu and Ngāti Haka - Rangiwai, Byron (Te Kaharoa, 2011)
This article argues that the racial discourses of the nineteenth century had an adverse impact on the ways in which Māori were treated and indeed, informed and justified colonial methods for separating Māori from their land. As a consequence of Pākeha representations of Māori as Other, Patuheuheu and Ngāti Haka - two closely related clans from the Tūhoe tribe - were subjected to oppressive practices which made it easy for Pākeha to unjustly procure land to the detriment of Patuheuheu and Ngāti Haka identity and wellbeing. This article examines Māori, Patuheuheu and Ngāti Haka land loss using multiple and interdisciplinary theoretical lenses, and posits that these losses were caused, in part, by Pākeha racism.